Review of Contrast Enhancement Techniques Based on Histogram Processing - Ray Pradhan, Satyajit; Sekhar Panda, Chandra (International Journal of Computer Sciences and Engineering, 2020)
Image enhancement is one of the basic steps used in digital image processing. Here the image is manipulated to make it more suitable than the original image for specific purposes. It is used to modify the contrast of an image. Here the intensity of the input image is manipulated to make the best use of available grayscale values. A wide range of contrast enhancement methods available work upon the histogram of an image to make the image visually suitable for either viewing or further development. We need to study and review different contrast enhancement techniques primarily operating on the histogram of an image. Depending on the nature of the technique these are classified into global and local contrast enhancement techniques. This paper focuses on a comparative study of contrast enhancement techniques and draws conclusions considering their pros and cons.